Pelatihan Pengelolaan Referensi Menggunakan Mendeley di Universitas Harapan Bangsa - Slamet Slamet; Iis Setiawan Mangku Negara; Arif Setia Sandi Ariyanto (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
ABSTRACT Managing references is an important part of preparing assignments and scientific work, especially in the higher education environment. This activity aims to provide additional insight for students at Harapan Bangsa University about managing reference sources in scientific work by utilizing the Mendeley application. This activity was carried out targeting students, especially final year students, to assist in the process of preparing the final assignment. Students can practice directly and operate Mendeley from the initial stages, starting with downloading applications, searching for a bibliography, and inputting sources of various references from books, journals, and websites. The obstacle found is that not all students know and understand the existence of a reference resource management application. The role of the lecturer is very influential in improving the quality of student scientific work so this activity is expected to be scheduled regularly, especially to help beginner and final-level students.